Redescription of leaf miners (Agromyzidae) infesting pods of legumes from India and Nepal - Thapa, Ram Bahadur (Our Nature, 2013)
Two species of pod flies under the genus Melanagromyza Hendel were reared, redescribed and illustrated from India. These were Melanagromyza albisquama (Malloch) and Melanogromyza obtusa (Malloch). Melanagromyza albisquama (Malloch) was reared from seeds of Alysicarpus moniliform Dc., Alysicarpus rugosus Dc. (Linn.), Alysicarpus vaginalis (Linn.) Dc. and Desmodium gangeticum Dc. from Uttar Pradesh India. This is a first report from India. The second species reared, re-described and illustrated from India was Melanagromyza obtusa (Malloch) from pods of Cajanus cajan (Linn.) Millsp. and Flemingia congesta Roxb. Melanagromyza obtusa (Malloch) was also reared from pods of Cajanus cajan (Linn.) Millsp. from Biratnagar, eastern Nepal (Thapa, 2000) and this is the first report from Nepal. Variation within these species, were also described and illustrated, with genitalia preparation. The biology of albisquama (Malloch) has been clarified from India (Thapa, 1991). Descriptions and genitalia illustration broadly agreed with the illustrations figured by (Spencer, 1963, 1977). Variation within the species was also studied by the author (Thapa, 1991). Sehgal (1987) had also collected and reared large series of this species from several localities in Terai and Kumaon and Garhwal regions of Northern India on its widely cultivated host plants, Cajanus cajan (Linn.) Millsp. and an alternate wild host Flemingia congesta Roxb. Spencer (1973, 1977) has listed Cajanus indicus Spreng, Flemingia sp. and Phaseolus radiatus Linn. as leguminous hosts of this species. Six new species of other stem flies infesting mostly legumes were also discovered under the genus Melanagromyza (stem flies) from Pantnagar, northen India. These were: M . pathaki new; M .glycini new species; M . denticulata Willd. new species; M . pisiphaga new species; M . sehgali new species ; M .vicivora new species.New names have been proposed to them as per International rules of Zoological Nomenclature. Thapa (2012) has redescribed M. sojae (Zehntner) under Melanagromyza Hendel from India and Nepal. DOI: http://dx.doi.org/10.3126/on.v10i1.7794